Increases in summer serum 25-hydroxyvitamin D (25OHD) concentrations in elderly subjects in São Paulo, Brazil vary with age, gender and ethnicity - Maeda, Sergio S (BioMed Central, 2010)
BACKGROUND: Hypovitaminosis D is a common condition among elderly individuals in temperate-climate countries, with a clear seasonal variation on 25 hydroxyvitamin D levels, increasing after summer and decreasing after winter, but there are few data from sunny countries such as Brazil. Many factors can interfere on vitamin D cutaneous synthesis. We aimed at studying the 25OHD variations during winter and summer in an outdoor physically active elderly population living in São Paulo city, and analysed their determining factors. METHODS: Ninety-nine individuals (52 women and 47 men, from 55 to 83 years old) from different ethnic groups were selected from an outdoor physical activity group. Data are reported as Mean ± SD, and we used Pearson Linear Correlation, Student's t-test for non-related samples, Chi-square (χ²) test and One-way ANOVA for analysis. RESULTS: Mean 25OHD value for the whole group was 78.9 ± 30.9 nmol/L in the winter and 91.6 ± 31.7 nmol/L in the summer (p = 0.005). Mean winter serum 25OHD concentrations were not different between men and women (81.2 ± 30.1 nmol/L vs. 76.7 ± 31.8 nmol/L, respectively), and 19.2% of the individuals showed values < 50 nmol/L. In the summer, we noticed an increase only for men (107.6 ± 31.4 nmol/L) compared to women (76.7 ± 24.0 nmol/L), and 6.5% showed values < 50 nmol/L. A decrease in the mean PTH in the summer compared to the winter was noticed, with PTH levels showing a relationship with 25OHD concentrations only in the winter (r = -0.208, p = 0.041). White individuals showed an increase in mean serum 25OHD in the summer (p = 0.016) which was not noticed for other ethnic groups (Asians, native Brazilians and blacks). An increase in 25OHD values in the summer was observed in the age groups ranging from 51-60 and 61-70 years old (p < 0.05), but not in the age group from 71 years old on. CONCLUSIONS: 25OHD values increased during the summer in elderly residents of São Paulo, but to different extents depending on ethnicity, gender and age. This season-dependent increase was noticed only among men, white and who were in the youngest group of individuals.